Faktor Konfirmatori Permainan Trapoly untuk Mengurangi Gangguan Kesehatan Mental Remaja di Makassar - Thaha, Irwan; Husna, Asmaul; Yusfitasari, Yusfitasari; Inayah, Nur Aulia; Mawaddah, Arini Ulfa; Ali, Muh.Yusuf (Universitas Cokroaminoto Palopo, 2024)
This study aims to analyze the factors that cause adolescent mental health disorders in Makassar City and evaluate the effectiveness of Trapoly games in reducing the rate of mental health disorders among these adolescents. The population of this study consisted of adolescents aged 15-19 years in Makassar City with a sample of 399 randomly selected people. The research phase involved the distribution of questionnaires including the DASS-21 scale as well as instruments for measuring factors causing adolescent mental health disorders and Trapoly playing experience, followed by Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and t-test tests. The results of EFA research show that social interaction factors, product quality factors, emotional intelligence factors, interactive factors, social influence factors and individual characteristic factors affect the effectiveness of Trapoly games. Furthermore, CFA identified the factors that most influence adolescent mental health disorders in Makassar City are school environment factors and peer environment factors and the factors that most affect the effectiveness of Trapoly games are social influence factors. The t-test analysis confirmed a significant difference between the rates of adolescent mental health problems before and after playing Trapoly. The results highlighted that Trapoly game has the potential to reduce the rate of adolescent mental health disorders in Makassar City.